2018
DOI: 10.15252/embj.201899763
|View full text |Cite
|
Sign up to set email alerts
|

Chemical genetic identification of CDKL 5 substrates reveals its role in neuronal microtubule dynamics

Abstract: Loss‐of‐function mutations in CDKL5 kinase cause severe neurodevelopmental delay and early‐onset seizures. Identification of CDKL5 substrates is key to understanding its function. Using chemical genetics, we found that CDKL5 phosphorylates three microtubule‐associated proteins: MAP1S, EB2 and ARHGEF2, and determined the phosphorylation sites. Substrate phosphorylations are greatly reduced in CDKL5 knockout mice, verifying these as physiological substrates. In CDKL5 knockout mouse neurons, dendritic microtubule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(120 citation statements)
references
References 66 publications
(89 reference statements)
4
108
0
Order By: Relevance
“…While the MH2 domain is highly conserved among all SMADs, the different structure of the MH1 domain of SMAD3, which does not contain the 30‐amino‐acid insert that is present in SMAD2 , could explain the specificity of the CDKL5‐dependent phosphorylation of SMAD3. Though recent observation has raised the possibility that the RPXSA motif might represent a consensus sequence for phosphorylation by CDKL5 , other studies have identified CDKL5 phosphorylation targets that do not contain this consensus motif , suggesting the presence of a different consensus sequence for CDKL5 phosphorylation or of a protein folding that creates a noncontiguous CDKL5 phosphorylation motif . SMAD3 seems to belong to this latter group because the MH1 domain does not present a RPXSA motif.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While the MH2 domain is highly conserved among all SMADs, the different structure of the MH1 domain of SMAD3, which does not contain the 30‐amino‐acid insert that is present in SMAD2 , could explain the specificity of the CDKL5‐dependent phosphorylation of SMAD3. Though recent observation has raised the possibility that the RPXSA motif might represent a consensus sequence for phosphorylation by CDKL5 , other studies have identified CDKL5 phosphorylation targets that do not contain this consensus motif , suggesting the presence of a different consensus sequence for CDKL5 phosphorylation or of a protein folding that creates a noncontiguous CDKL5 phosphorylation motif . SMAD3 seems to belong to this latter group because the MH1 domain does not present a RPXSA motif.…”
Section: Discussionmentioning
confidence: 96%
“…The way in which CDKL5 deficiency affects neuronal maturation is starting to be defined progressively with the identification of some of the molecular mechanisms underlying CDKL5 functions. CDKL5 forms a complex with PSD‐95 and NGL‐1 at the spine level to regulate spine morphology and maintenance , and with IQ domain‐containing GTPase‐activating protein 1 (IQGAP1) and MAP1S to regulate microtubule dynamics and stability . Although data clearly suggest that CDKL5 is important for correct neuronal maturation , the role of CDKL5 in the maintenance of neuron survival has been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, given that KCC2 has not been identified as a direct substrate of CDKL5 (Baltussen et al, 2018;Munoz et al, 2018), the CDKL5-dependent regulation of pKCC2 might be mediated indirectly through the action of protein kinase C, which has been reported to interact with CDKL5 and phosphorylate KCC2 at S940 (Lee et al, 2007;Wang et al, 2012). Although we did not find any alteration in the expression of proteins related to excitation/inhibition (E/I) balance, such as pKCC2-T1007, NKCC1, GABAA receptor, GAD2, vGAT, vGluT2 and CB1R, in the cortex at P12, other players, such as NMDA receptors, AMPA receptors and parvalbumin, could still play a role in CDKL5-deficiency-induced E/I imbalance (Pizzo et al, 2016;Okuda et al, 2017;Tang et al, 2017;Yennawar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Writing in The EMBO Journal , two groups simultaneously reveal the first physiological substrates for CDKL5, including potential new biomarkers for reporting cellular CDKL5 activity. Using distinct, but highly complementary mass spectrometry (MS)‐based phosphoproteomics approaches, the laboratories of John Rouse and Matthias Trost (Muñoz et al , ), and Sila Ultanir (Baltussen et al , ) evaluate functional consequences of CDKL5‐catalysed substrate phosphorylation and its loss in cells lacking functional CDKL5. These findings will be critical for understanding microtubule dynamics and cilium‐based signalling in CDD cell models, including neurons from patients with pathological CDKL5 mutations.…”
Section: Physiological Cdkl5 Substrates Control Cytoskeletal Functionmentioning
confidence: 99%
“…In the case of the microtubule-binding protein MAP1S, a biological function for phosphorylation was confirmed in elegant murine follow-up experiments, exploiting phospho-specific MAP1S antibodies to demonstrate that phosphorylation on Ser812 (equivalent to human Ser900) was impaired in microtubule binding in vitro, consistent with a significant reduction in microtubule dynamics in living cortical neuron dendrites derived from CDKL5 knockout mice (Baltussen et al, 2018). In order to probe signalling with additional reagents, both studies made use of additional phosphospecific antibodies.…”
mentioning
confidence: 93%